Transformasi Digital Pendidikan Generative AI untuk Guru SMA ALIA ISLAMIC SCHOOL Menggunakan Aplikasi Teachy - Ade Putra Prima Suhendri; Meidy Fajar Wahyu; Amin Hidayat (CV. Multi Kreasi Media, 2025)
The development of Artificial Intelligence (AI) technology opens greatopportunities for educational transformation. However, AI utilization in schoolsstill faces challenges, particularly the low technology literacy among teachers. ThisCommunity Service Program (PKM) aims to enhance the competency of SMA AliaIslamic School teachers in utilizing Generative AI technology, specifically theTeachy platform, for creating learning materials. The implementation methodsinclude interactive lectures, simulations, hands-on practice, group discussions, andevaluation. The activity was conducted on April 24, 2025, at SMA Alia IslamicSchool, Tangerang, with 18 teacher participants from various subjects. The resultsshowed significant improvement in teachers' understanding of AI concepts and theirapplications in education. Teachers successfully practiced creating educationalmaterials using AI-based platforms independently. This activity also increasedteachers' motivation and confidence in integrating digital technology into thelearning process. Positive impacts were evident from the creation of moreinteractive and engaging learning media that can be used in both online and offlinelearning. The conclusion of this activity is that AI training proved effective insupporting digital transformation in educational environments. Recommendationsfor program sustainability include expanding training coverage, continuousmentoring, developing technology-based curricula, collaboration with universities,and strengthening school digital infrastructure. This PKM activity contributessignificantly to preparing teachers to face educational challenges in the digital erawhile maintaining Islamic values as the foundation of education at the school.